NOTIFICATION !!! - Papers Retrieved (European Scientific Journal, ESJ, 2014)
All the content of this special edition is retrieved from the conference proceedings published by the European Scientific Institute, ESI. http://eujournal.org/files/journals/1/books/emf.vol.3.pdf The European Scientific Journal, ESJ, after approval from the publisher re publishes the papers as quality scientific articles in Special edition.